Privileged metal cluster complexes - Lin, Shiquan; Li, Dan; Zhang, Dandan; Geng, Lijun; Jia, Yuhan; Wang, Weizhe; Cheng, Longjiu; Khanna, Shiv N; Luo, Zhixun (Chemical science (Cambridge), 2025)
Clusters are a prominent subject of interest in modern chemistry research, bridging atoms and materials or catalysts. Metal coordination and metal-metal bonding are crucial in determining the chemical structures and properties of metal clusters; however, formulating a universal principle for assessing their electronic activity remains challenging. Utilizing self-developed mass spectrometry, this study examines the gas-phase reactions of rhodium and platinum clusters with common ligand molecules in forming metal complexes. We find that the Rh n ± ( n = 1-35) and Pt n ± ( n = 3-20) clusters readily react with CO and NO to form highly-selective products of cluster complexes. This illustrates the size-dependent saturable effect of sequential coordination, which is rooted in cluster stability alongside concurrent electron delocalization and local bonding. We introduce a new electronic rule, termed the electronic " A " rule, to understand the adaptive balance of electron delocalization and averaged local bonding in stabilizing metal clusters, whether they are coordinated with ligands or not. Gas-phase reactions of rhodium and platinum clusters with common ligand molecules in forming metal complexes, showing privileged cluster complexes with adaptive electron delocalization.